Intraoperative evaluation of the effects of femoral component offset and head size on joint stability in total hip arthroplasty. (18th January 2017) - Jinno, Tetsuya; Koga, Daisuke; Asou, Yoshinori; Morita, Sadao; Okawa, Atsushi; Muneta, Takeshi
Purpose: To evaluate intraoperatively the effects of femoral offset and head size on stability of the hip joints in total hip arthroplasty (THA) via posterior approach. Methods: Thirty cementless THAs were included in this study. After acetabular shell and femoral broach fixation, trial reduction was repeated using a femoral neck (5- to 8-mm higher or standard offset) and a head (26 mm or 32 mm). To evaluate joint stability, range of internal rotation (IR) in hip flexion prior to posterior subluxation and range of external rotation (ER) in hip extension were measured. Results: The high-offset neck provided significantly (approximately 10°) greater range of IR to subluxation than the standard-offset neck. No hips ended in anterior subluxation by ER. The head size did not have significant effects on the stability. Conclusion: Results suggest that the 5- to 8-mm greater femoral offset might be effective in preventing instability in primary THA.